2001
DOI: 10.1590/s0004-27302001000200009
|View full text |Cite
|
Sign up to set email alerts
|

Estudo morfométrico do fígado de ratos submetidos a doses supra-fisiológicas de tiroxina

Abstract: RESUMOTireotoxicose é o estado hipermetabólico causado pelo excesso de hormônios tireoidianos circulantes, que exercem sua ação praticamente em todos os tecidos. No presente estudo avaliou-se, por métodos estereológicos, o fígado de ratos tratados com doses supra fisiológicas de T4 (20µg/100g de peso de corporal) durante 20 dias. Os níveis séricos de T4 desses animais estavam significativamente elevados (p=0,02). Houve tendência a perda de peso corporal dos animais tratados em relação ao grupo controle (p=0,10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
0
7
0
9
Order By: Relevance
“…Considering that cholestasis involves bile ducts, significant changes found in our study might indicate that administration of TP altered the concentration of bile ducts conveyed by said. Moreover, it might have an increase in the volume of capillaries sinusoids by a hepatic congestion (Engelman et al, 2001). Bento-Silva et al (2010) described the occurrence of hepatic congestion in rats that received administration testosterone undecanoate.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that cholestasis involves bile ducts, significant changes found in our study might indicate that administration of TP altered the concentration of bile ducts conveyed by said. Moreover, it might have an increase in the volume of capillaries sinusoids by a hepatic congestion (Engelman et al, 2001). Bento-Silva et al (2010) described the occurrence of hepatic congestion in rats that received administration testosterone undecanoate.…”
Section: Discussionmentioning
confidence: 99%
“…Rodents have been increasingly used in this kind of study, once they are prospective regarding the action of chemicals in humans. Furthermore, the organs that are considered vital are good histological biomarkers in toxicity assays [24].…”
Section: Doi: 107243/2055-091x-4-9mentioning
confidence: 99%
“…The histological analysis showed that the hepatic tissue of the individuals belonging to the three control groups was intact, with preserved hepatocytes, arranged in cords and permeated by Kupffer cells, also intact [21,24].…”
Section: Livermentioning
confidence: 99%
See 1 more Smart Citation
“…Alterações crônicas no fígado podem estar presentes e variam de fibrose portal leve até cirrose e redução da glutationa, com aumento de radicais reativos de oxigênio. 7,8,9 Nem sempre as alterações supracitadas são diagnosticadas pela ultrassonografia abdominal, não sendo possível descartar uma hepatopatia difusa quando o órgão apresenta-se normal ao exame, uma vez que se pode não ocorrer distorção da textura ou da arquitetura interna do parênquima. 10,11 O acúmulo de gordura promove maior reflexão das ondas sonoras elevando a ecogenicidade do parênquima hepático em relação ao ligamento falciforme.…”
Section: Introductionunclassified